Knowledge, Anxiety, and practice during the COVID-19 crisis among HCWs in Saudi Arabia - Salah Alshagrawi; Sultan Alhowti (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The rapid and widespread of COVID-19 has caused distress and havoc among people in all walks of life. Such impact has been more pronounced among HCWs. We sought to examine how health care workers (HCWs) knowledge about COVID-19 and perceived anxiety can influence preventive practices. MATERIALS AND METHODS: In this cross-sectional study a multiple regression analysis was applied to examine the relationship between knowledge, anxiety, and preventive practices among 267 participants work in different settings in a variety of health care organizations in different regions in Saudi Arabia. To estimate potential associations, a multiple regression analysis was applied. Standardized beta-coefficients and their 95% confidence intervals were estimated to examine the outcome variable and the predictors' associations. RESULTS: Our findings shows that HCWs had high levels of knowledge about COVID-19, perceived anxiety, and preventive practices. In examining the relation between HCWs characteristics and their knowledge about COVID-19, older HCWs have been shown to have higher knowledge compared to younger HCWs. Finally, the model to estimate the impact of knowledge about COVID-19 and perceived anxiety on preventive practice showed that both have a significant impact. CONCLUSIONS: HCWs tendency to adhere to preventive practices is related to their levels of knowledge and perceived anxiety. Such a relationship can inform administrators and policymakers in the health care field to design health promotion campaigns to ensure all HCWs are aware of the nature of communicable diseases and the risk they might entail.